Association between cardiorespiratory fitness, obesity, and incidence of atrial fibrillation. (December 2020) - Kamil-Rosenberg, Shirit; Kokkinos, Peter; Grune de Souza e Silva, Christina; Yee, Win Leth Shwe; Abella, Joshua; Chan, Khin; Myers, Jonathan
Abstract: Background: The interaction between cardiorespiratory fitness (CRF) and incidence of atrial fibrillation (AF) and the interaction between obesity and incidence of AF have been explored separately. Therefore, we evaluated the association between CRF, body mass index (BMI), and risk of developing AF in a cohort of middle-aged and older US Veterans. Methods: Symptom limited exercise tests (ETT) were conducted among 16, 397 Veterans (97% male) from January 9, 1987 to December 31, 2017. No history of AF was evident at the time of the ETTs. CRF was expressed as quartiles of peak metabolic equivalents (METs) achieved within each age decile. Weight status was classified as normal (BMI < 25 kg/m 2 ), overweight (BMI 25–30 kg/m 2 ), obese (BMI 30–35 kg/m 2 ), or severely obese (BMI > 35 kg/m 2 ). Multivariable Cox proportional hazards regression models were used to compare the association between BMI, CRF categories, and incidence of AF. Results: Over a median follow-up of 10.7 years, 2, 155 (13.1%) developed AF. Obese and severely obese subjects had 13% and 32% higher risks for incidence of AF, respectively, vs. normal weight subjects. Overweight and obese subjects in the most fit quartile had 50% decline in AF risk compared to the least-fit subjects. Severely obese subjects had marked increases in AF risk ( 50–60%) regardless of fitness level. Risk of developing AF increases with higher BMI and lower CRF. Conclusion: Improving CRF should be advocated when assessing those at risk for developing AF.